Devitalized Xenogenic Arteries: Transplantation Experience - Shevchenko, Eugeniy V.; Gorlenko, Anna A.; Byzov, Denis V. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):176.